Analisis Pengaruh Indeks Pembangunan Manusia, Laju Pertumbuhan Penduduk, dan Tingkat Pengangguran Terbuka terhadap Kemiskinan di DKI Jakarta - Rama Bhaskara Praja; Masruri Muchtar; Pardomuan Robinson Sihombing (Ecoplan, 2023)
The poverty rate has increased rapidly again due to the Covid-19 Pandemic. DKI Jakarta is one of the top 5 provinces with the lowest poverty rate in Indonesia, even though it has high complexity in administering its government. Because of these achievements, this study aims to find factors that influence poverty so that it can become a reference for other local governments in alleviating poverty. This research was conducted using panel data regression with a fixed effect model. The results showed that simultaneously poverty headcount index in the t-1 period, human development index (HDI), open unemployment rate, and population growth rate significantly affect the poverty headcount index. While partially, open unemployment and population growth rate positively and significantly affect the poverty headcount index. On the other hand, the poverty headcount index in the t-1 period and HDI positively and insignificantly affect the poverty headcount index. This research shows that local governments must focus more on policies to reduce unemployment and population growth rate in the context of alleviating poverty.